VOLLEY BALL PASSING PORTABLE (VP2) UNTUK MENINGKATKAN KEMAMPUAN MENERIMA BOLA PEMAIN OLAHRAGA SISWA SMA - Prenika, Wulan; Kesumawati, Selvi Atesya; Septaliza, Dewi; Sukmawati, Noviria (Fakultas Ilmu Keolahragaan Unimed, 2025)
ABSTRACT Volleyball extracurricular activities are among the most popular sports in schools; however, the fundamental technical skills of extracurricular participants are often suboptimal due to (1) limited training time, (2) insufficient equipment that is both effective and safe to use, and (3) reliance on partners or coaches to conduct passing drills. This study aims to develop a volleyball forearm passing training aid, the “Volley Ball Passing Portable (VP2),” for extracurricular participants at senior high schools and vocational high schools. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The small-scale trial involved 35 male and female volleyball extracurricular participants from SMK Negeri 1 Gelumbang, while the large-scale trial involved 61 participants from SMA Negeri 1 and SMA PGRI Gelumbang. Expert validation involved four experts consisting of two training media experts, one volleyball game expert, and one coach. The research instrument used an expert assessment rubric with a rating scale. Data analysis was conducted using the Content Validity Index (CVI) and Content Validity Ratio (CVR), yielding a CVI score of 3.915 and a CVR score of 0.83, indicating a high level of validity. These results suggest that the VP2 training media can proceed to the field trial (implementation) stage with recommended improvements. Keywords: Volleyball, Portable, Extracurricular.